A Self‐Report Survey: Australian Clinicians' Attitudes Towards Progress Monitoring Measures. (11th July 2018) - Chung, Jennifer; Buchanan, Ben
Abstract : Objective: Research supports an association between regularly administering standardised measures to assess client progress (progress monitoring) and improved treatment outcomes. However, some research suggests clinicians often rely heavily and solely on clinical judgement when making treatment decisions. This study was the first to explore psychologists' implementation of progress monitoring, within an Australian clinical context. Method: A self‐report survey investigated Australian psychologists' ( N = 208; gender and age proportional to national representation) attitude, awareness, use, motives, and barriers towards implementing standardised assessment and progress monitoring. The survey comprised of the Attitudes towards Standardised Assessment Scales, and existing literature on progress monitoring implementation. Results: Ninety‐eight per cent of psychologists were aware of progress monitoring measures, and 69% reported using them in practice. Majority of progress monitoring users rated these measures as very useful (51%) and over one third (39%) used them with most of their clients. Contrary to the hypothesis, a t ‐test demonstrated that attitude towards standardised assessment did not differ between progress monitoring users and non‐users. Among the clinicians who have not implemented progress monitoring, time barriers were rated as most important. Conclusion: This study demonstrates that although awareness of progress monitoring may be widely known, perceived barriers may outweigh the potential benefits for some. It is also concluded that further qualitative research is needed to adequately understand these barriers and their importance. Future interventions may then promote evidence‐based recommendations and focus on the practicality, utility, and workflow difficulties associated with incorporating progress monitoring.